2014
DOI: 10.1007/s10792-014-9926-8
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification versus peripheral iridotomy in the management of chronic primary angle closure: long-term follow-up

Abstract: Primary angle closure occurs as a result of crowded anterior segment anatomy, causing appositional contact between the peripheral iris and trabecular meshwork, thereby obstructing aqueous outflow. Several studies highlight the role of the crystalline lens in its pathogenesis. The objective of this work is to compare the long-term efficacy of phacoemulsification versus laser peripheral iridotomy (LPI) in the management of chronic primary angle closure (CPAC). Prospective case-control study with 30 eyes of 30 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…A total of four studies [ 22 , 23 , 25 , 28 ] recorded the ACD of the two groups three months after the operation. There was significant heterogeneity between the studies ( P < 0.00001 and I 2 = 99%), so the random effect model was used for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of four studies [ 22 , 23 , 25 , 28 ] recorded the ACD of the two groups three months after the operation. There was significant heterogeneity between the studies ( P < 0.00001 and I 2 = 99%), so the random effect model was used for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-four full-text articles were identifed as potentially relevant for analysis in terms of the inclusion and exclusion criteria. Finally, eight studies [22][23][24][25][26][27][28][29] involving 894 eyes were included in the analysis. Tere was no signifcant diference in age, gender composition ratio, and IOP before treatment between the two groups (P > 0.05).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, prior studies have shown that PAC spectrum eyes have more anteriorly positioned crystalline lenses than normal eyes [13–15]. Cataract extraction (CE) with a thin intraocular lens (IOL) implantation may open the angle by deepening the ACA, repositioning the ciliary processes posteriorly, and reducing IOP, making it a potentially viable surgical treatment for PAC spectrum patients [7, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Ten korzystny stosunek ryzyka do korzyści sprawia, iż operacja usunięcia zaćmy jest potencjalnie skuteczną strategią leczenia u pacjentów ze współistniejącymi jaskrą i zaćmą, zarówno jako pojedynczy zabieg, jak i łączony z zabiegiem przeciwjaskrowym (MIGS, minimally invasive glaucoma surgeries). Dodatkowo zabieg usunięcia zaćmy w większości przypadków ma udowodnione znaczenie w obniżaniu IOP, dlatego też rośnie przekonanie, iż sama fakoemulsyfikacja zabieg uSunięcia zaćMy a iOp Wpływ zabiegu usunięcia zaćmy na zmiany w IOP był i nadal jest tematem wielu badań skupiających się na różnych typach jaskry[6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Dyskusyjne pozostaje jednak, jak silne są: ta zależność, efekt oraz znaczenie kliniczne.…”
unclassified